Correlation between Genetic Polymorphism of CYP2A13 Genotype and Lung Cancer in Female Passive Smokers - Nurul Ramadhani; Noni Novisari Soeroso; Setia Putra Tarigan; Putri Chairani Eyanoer; Hidayat Hidayat (Cell and BioPharmaceutical Institute, 2022)
Background: Nicotine is metabolized to cotinine by cytochrome P450 enzyme, and this enzyme is involved in the activation of toxic and carcinogenic substances. The aim of this research was to assess the relationship between genetic polymorphism of CYP2A13 and lung cancer incidence in female passive smokers.Materials and methods: This research was a case-control study that involved 104 research subjects. Subjects were recruited through purposive sampling technique from 2 hospitals in Medan, North Sumatra, Indonesia. The case population consisted of female passive smokers with lung cancer and the control population consisted of female passive smokers without lung cancer. All research subjects underwent blood sampling for genomics DNA extraction and CYP2A13 genotyping by polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP). Data was analyzed by conditional logistic regression by Epi Info 7.0 software.Results: Among 104 subjects, 26 (25%) individuals were heterozygous, 76 (73%) individuals were wild type, and 2 (2%) were mutant for the 257Cys allele. There was a significant correlation between CYP2A13 genotype and lung cancer incidence (p-value<0.05). Female passive smokers with CT genotype had 2.7 greater risk of developing lung cancer than those with CC genotype (wild type). The C allele had more frequency and 1.6 times higher risk of lung cancer compared to T allele with a wide confidence range (0.73–3.52).Conclusion: There was a significant correlation between CYP2A13 polymorphism and lung cancer incidence in female passive smokers.Keywords: polymorphism, CYP2A13, PCR-RFLP, female passive smoker, lung cancer